Front Cover: An Anomalous Antiaromaticity That Arises from the Cycloheptatrienyl Anion Equivalent (Eur. J. Org. Chem. 33/2018). Issue 33 (19th July 2018) - Uehara, Keiji; Mei, Peifeng; Murayama, Tomohisa; Tani, Fumito; Hayashi, Hironobu; Suzuki, Mitsuharu; Aratani, Naoki; Yamada, Hiroko
Abstract : The Front Cover shows a fused azulene dimer helicate prepared by simple Suzuki–Miyaura coupling with a background showing a spiral staircase. The newly formed central seven‐membered ring (highlighted in yellow) exhibits a positive NICS value that arises from the cycloheptatrienyl anionic structure with an anomalous antiaromatic behavior. This new concept will be important for the molecular design of novel π‐conjugated materials based on polycyclic aromatic hydrocarbons containing five‐ and seven‐membered rings. More information can be found in the Communication by N. Aratani, H. Yamada et al.